OXA β-lactamases from Acinetobacter spp. are membrane bound and secreted into outer membrane vesicles - Capodimonte, Lucía Soledad (2024)
β-lactamases from Gram-negative bacteria are generally regarded as soluble, periplasmic enzymes. NDMs have been exceptionally characterized as lipoproteins anchored to the outer membrane. A bioinformatics study on all sequenced β-lactamases was performed that revealed a predominance of putative lipidated enzymes in the Class D OXAs. Namely, 60% of the OXA Class D enzymes contain a lipobox sequence in their signal peptide, that is expected to trigger lipidation and membrane anchoring. This contrasts with β-lactamases from other classes, which are predicted to be mostly soluble proteins. Almost all (>99%) putative lipidated OXAs are present in Acinetobacter spp. Importantly, we further demonstrate that OXA-23 and OXA-24/40 are lipidated, membrane-bound proteins in Acinetobacter baumannii. In contrast, OXA-48 (commonly produced by Enterobacterales) lacks a lipobox and is a soluble protein. Outer membrane vesicles (OMVs) from A. baumannii cells expressing OXA-23 and OXA-24/40 contain these enzymes in their active form. Moreover, OXA-loaded OMVs were able to protect A. baumannii, Escherichia coli, and Pseudomonas aeruginosa cells susceptible to piperacillin and imipenem. These results permit us to conclude that membrane binding is a bacterial host-specific phenomenon in OXA enzymes. These findings reveal that membrane-bound β-lactamases are more common than expected and support the hypothesis that OMVs loaded with lipidated β-lactamases are vehicles for antimicrobial resistance and its dissemination. This advantage could be crucial in polymicrobial infections, in which Acinetobacter spp. are usually involved, and underscore the relevance of identifying the cellular localization of lactamases to better understand their physiology and target them.